Transient receptor potential canonical 5 channels plays an essential role in hepatic dyslipidemia associated with cholestasis - Khadija M. Alawi (Nature Portfolio, 2017)
Abstract Transient receptor potential canonical 5 (TRPC5), a calcium-permeable, non-selective cation channel is expressed in the periphery, but there is limited knowledge of its regulatory roles in vivo. Endogenous modulators of TRPC5 include a range of phospholipids that have an established role in liver disease, including lysophosphatidylcholine (LPC). Cholestasis is characterized by impairment of excretion of bile acids, leading to elevation of hepatic bile acids. We investigated the contribution of TRPC5 in a murine model of cholestasis. Wild-type (WT) and TRPC5 knock-out (KO) mice were fed a diet supplemented with 0.5% cholic acid (CA) for 21 days. CA-diet supplementation resulted in enlargement of the liver in WT mice, which was ameliorated in TRPC5 KO mice. Hepatic bile acid and lipid content was elevated in WT mice, with a reduction observed in TRPC5 KO mice. Consistently, liver enzymes were significantly increased in cholestatic WT mice and significantly blunted in TRPC5 KO mice. Localized dyslipidaemia, secondary to cholestasis, was investigated utilizing a selected lipid analysis. This revealed significant perturbations in the lipid profile following CA-diet feeding, with increased cholesterol, triglycerides and phospholipids, in WT, but not TRPC5 KO mice. Our results suggest that activation of TRPC5 contributes to the development of cholestasis and associated dyslipidemia. Modulation of TRPC5 activity may present as a novel therapeutic target for liver disease.